Factors Affecting the Capital Structure of the Textile Industry in Bangladesh: An Inferential Study - Ashraf, Aysha; Rezina, Sonia (Financial Risk and Management Reviews, 2020)
The main objective of the study is to recognize the major factors influencing the capital structure of the textile firms and to identify the association among them from the context of Bangladesh. The researchers reviewed different conditional theories of capital structure before identifying the determinants of the textile firms. For this purpose, panel data for A-category listed textile companies of the Dhaka Stock Exchange were selected. The study developed multiple regression models for the period 2008 to 2017. Key -independent variables include firm profitability, tangibility, growth, age, liquidity and Size. Leverage ratio was used as the dependent variable. The study explored that profitability; firm size and liquidity have significant positive relationship with the debt ratio, which is consistent with the Trade-off theory. On the other hand, tangibility, growth rate and age are not significantly related with the said ratio. The findings of this study will help financial managers to make the right decisions on fund borrowing and equity financing. Then they can use borrowing in a proper way to support the market value of their companies.